Violence, law, and women's rights in South Asia - Goonesekere, Savitri (Sage Publications, 2004)
Overview : reflections on violence against women and the legal systems of some South Asian countries / Savitri Goonesekere -- Violence against women and the Indian law / Kirti Singh -- Violence against women : the legal systems and institutional responses in Pakistan / Hina Gilani and Emam M. Ahmed -- Sri Lanka : the law's response to women victims of violence / Shyamala Gomez and Mario Gomez